2020
DOI: 10.3389/fmicb.2020.575287
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Vibrio Communities and Abundance in Dongshan Bay, South of China

Abstract: The Vibrio genus inhabit estuarine and marine ecosystem throughout the world and can cause severe infections in humans and animals. Previous studies have demonstrated the dynamics of Vibrio at both community and population levels and assessed the close relationship between environmental factors and Vibrio diversity and abundance, such as temperature, salinity, and dissolved oxygen. It is also generally believed that aquaculture is the fastest-growing food sector, which is also applying great environmental impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 61 publications
2
25
0
Order By: Relevance
“…Mariculture is one of the main reasons due to low water exchange and large inputs of animal food and excrements in this area. Our previous study [52] confirmed that input of nutrients resulted in the highest diversity and significant temporal changes of the Vibrio community in summer. As a consequence, factors affecting the health of this important coastal ecosystem are constantly changing, urging to better understand the dynamics of especially pathogenic Vibrio species.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Mariculture is one of the main reasons due to low water exchange and large inputs of animal food and excrements in this area. Our previous study [52] confirmed that input of nutrients resulted in the highest diversity and significant temporal changes of the Vibrio community in summer. As a consequence, factors affecting the health of this important coastal ecosystem are constantly changing, urging to better understand the dynamics of especially pathogenic Vibrio species.…”
Section: Discussionsupporting
confidence: 73%
“…Water temperature, pH, salinity, dissolved oxygen (DO), and total dissolved solids (TDS) were measured in situ at each sampling site with a multiparameter water quality checker (Horiba U-50, Horiba Co., Kyoto, Japan). Chemical parameters comprised concentrations of nitrate (NO 3 − ), nitrite (NO 2 − ), ammonium nitrogen (NH 4 + ), and phosphate (PO 4 3− ) which were measured using standard protocols [52] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations